Climatic habitat regulates the radial growth sensitivity of two conifers in response to climate change - Ruhong Xue; Liang Jiao; Peng Zhang; Xuge Wang; Qian Li; Xin Yuan; Zhengdong Guo; Le Zhang; Yarong Qin (Forest Ecosystems)
The survival and mortality of conifer trees in response to climate change, particularly drought stress, have received considerable attention. However, it is crucial to explore the growth dynamics of the same conifer species in response to climate change in different climatic habitats. In this study, we aimed to quantify variations in the radial growth processes of conifer species, analyze their resilience during drought periods under different climatic habitats, and assess the impact of climate adaptation on conifer growth. We focused on two conifer species, Picea crassifolia (spruce) and Pinus tabuliformis (pine), which are distributed in both a humid habitat and a dry habitat in the northeastern Tibetan Plateau. Growth and resilience dynamics were identified across both climatic habitats and the contributions of temperature and moisture to the growth of the two species were simulated under drought stress using the VS-oscilloscope model. Spruce growth exhibited significant variability between climatic habitats. Specifically, the spruce growth rate declined in response to drought in the dry habitat (−0.91 ​cm2 per decade, p ​< ​0.01). In contrast, pine growth remained relatively stable (humid habitat: −0.03 ​cm2 per decade; dry habitat: 0.25 ​cm2 per decade, p ​> ​0.01), although it still responded to stress during the growing season (p ​< ​0.05). Furthermore, spruce displayed reduced resistance during stress in dry habitats (−30.11%), while pine exhibited an enhanced recovery of growth rates to ensure survival (+39.62%). The climate adaptation strategies of the species were linked to the contribution of temperature and moisture to their growth rates. Moisture is critical for the growth recovery of both conifers in dry habitats when temperature-associated growth displays a ‘bimodal’ pattern during the growing season. These findings have significant ecological implications for understanding conifer forest processes in the context of global climate change.